2008
DOI: 10.1152/ajplung.00071.2008
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase D signaling in serotonin-induced mitogenesis of pulmonary artery smooth muscle cells

Abstract: (7), has been increasingly associated with pulmonary hypertension (2, 4, 9, 30), and it is recognized that hyperplasia of SMCs accompanies the pathology of pulmonary hypertension (5, 10, 22). 5-HT initiates its SMC mitogenic action through both 5-HT receptors and the 5-HT transporter (5-HTT) (7) that are present on the cell membrane in close proximity to membrane structural lipids that include phosphatidylcholine. Through the receptor and transporter ligands, 5-HT produces SMC proliferation via combinatorial a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2009
2009
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…This provides direct evidence that JNK regulates Akt. We (17) also have previously found that activation of PLD by 5-HT occurs through the 5-HT 2A receptor and, like JNK, requires a mechanism that is PI3K-independent. We do not presently know whether the JNK pathway might participate in the activation of PLD by 5-HT.…”
Section: Discussionsupporting
confidence: 64%
“…This provides direct evidence that JNK regulates Akt. We (17) also have previously found that activation of PLD by 5-HT occurs through the 5-HT 2A receptor and, like JNK, requires a mechanism that is PI3K-independent. We do not presently know whether the JNK pathway might participate in the activation of PLD by 5-HT.…”
Section: Discussionsupporting
confidence: 64%
“…Although all known classic psychedelics produce their behavioral effects through activation of 5-HT 2A receptors, they also have significant 5-HT 2B receptor agonist activity at the doses necessary for behavioral effects. Activation of 5-HT 2A receptors directly in certain tissues including vascular, placental, and cancers can also have a proliferative effect (Sonier et al, 2005;Göoz et al, 2006;Liu and Fanburg, 2008;Chen et al, 2014), suggesting that the classic psychedelics may also have an effect on these processes. The molecular mechanisms underlying the proliferative effects largely appear to involve activation of ERK/ MAPK signaling downstream from the receptor.…”
Section: Effects On Cell Differentiation and Growthmentioning
confidence: 99%
“…33 In light of these findings, it can be anticipated that Src via recruitment of PKC or some other serine/threonine kinases mediates VEGF-induced PLD1 activation in stimulating HRMVEC angiogenic responses. Because PLD1 generates PA, a potent mitogen, 27 one could also expect that PA itself may be mediating the VEGF effects on HRMVEC proliferation, migration, and tube formation. However, this scenario appears unlikely as inhibition of PAP abrogated the VEGF-induced HRMVEC angiogenic responses.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, either 1-butanol (0.25%), the pharmacologic inhibitor of PLD1, 26 or PLD1 depletion by its siRNA attenuated VEGF-induced HRMVEC DNA synthesis, migration, and tube formation ( Figure 1B-D). Because activation of PLD1 generates phosphatidic acid (PA), a potential mitogen, 27 we asked the question whether PA or its conversion to diacylglycerol (DAG) is needed for VEGF-induced HRMVEC DNA synthesis, migration, and tube formation. To After exposure to 75% oxygen, the mice pups were returned to normoxia, administered 1 g of Scr, Src, PLD1, or PKC␥ siRNA at P13, P14, and P15 by intravitreal injections, and at P17 pups were anesthetized, perfused with FITC-dextran, sacrificed, enucleated, retinas were isolated, and flat mounts of whole retina were examined for retinal neovascularization (B).…”
Section: Pld1-pkc␥ Signaling In Retinal Angiogenesis 1381mentioning
confidence: 99%